2016
DOI: 10.1113/ep085749
|View full text |Cite
|
Sign up to set email alerts
|

Humanin prevents brain mitochondrial dysfunction in a cardiac ischaemia–reperfusion injury model

Abstract: New Findings r What is the central question of this study?Myocardial ischaemia-reperfusion (I/R) injury causes interference in the systemic circulation and damages not only the heart but also several vital organs, including the brain. Recently, a novel peptide called humanin has been shown to exert potent neuroprotective effects. However, the effect of humanin on the brain during cardiac I/R injury has not yet been investigated. r What is the main finding and its importance?The I/R injury caused blood-brain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…It has been documented that humanin may alter mitochondrial oxidative phosphorylation and ATP production; however, the exact molecular mechanisms are not well understood (8). A study by Kumfu et al (35) reported that humanin may prevent brain mitochondrial dysfunction in a model of cardiac ischemia-reperfusion injury. The results of the present study demonstrated that HNG inhibited mitochondrial dysfunction-mediated apoptosis via Jak2/Stat3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that humanin may alter mitochondrial oxidative phosphorylation and ATP production; however, the exact molecular mechanisms are not well understood (8). A study by Kumfu et al (35) reported that humanin may prevent brain mitochondrial dysfunction in a model of cardiac ischemia-reperfusion injury. The results of the present study demonstrated that HNG inhibited mitochondrial dysfunction-mediated apoptosis via Jak2/Stat3.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were attenuated by HNG treatment, which protects mitochondria through decreased complex I activity [101]. Similarly, HNG protects brain mitochondria during AMI and MRI, reducing tau hyperphosphorylation, Aβ accumulation and apoptosis [102,103]. However, in the porcine model system, the cardioprotective effect of HNG treatment was observed only for short-term ischemia, with no significant protective effect with prolonged ischemia [104].…”
Section: Association Between Mdps and Cvdsmentioning
confidence: 99%
“…protects brain mitochondria during AMI and MRI, reducing tau hyperphosphorylation, Aβ accumulation and apoptosis [102,103] inhibits platelet aggregation, P-selectin expression, αIIbβ3 activation and adhesion under flow conditions; enhances tubulin acetylation and inhibits microtubule depolymerization [105]…”
Section: Association Between Mdps and Cvdsmentioning
confidence: 99%
“…Brain I/R injury is a complex pathophysiological process. Brain blood flow interruption and reperfusion damage the brain cells is a rapid cascade reaction [12,13]. This cascade reaction includes many links, such as energy metabolism, cytotoxicity, increased release of excitatory amino acids, intracellular calcium homeostasis, free radical production, and activation of apoptotic genes [14].…”
Section: Introductionmentioning
confidence: 99%